Differential Impact of Glucose Administered Intravenously and Orally on Circulating miR-375 Levels in Human Subjects - Yan, Xin; Wang, Zhen; Westberg-Rasmussen, Sidse; Tarbier, Marcel; Rathjen, Thomas; Tattikota, Sudhir G; Peck, Bailey C E; Kanke, Matt; Oxvig, Claus; Frystyk, Jan; Starup-Linde, Jakob; Sethupathy, Praveen; et al. (The journal of clinical endocrinology and metabolism, 2017)
BackgroundTo date, numerous nucleic acid species have been detected in the systemic circulation including microRNAs (miRNAs); however, their functional role in this compartment remains unclear.ObjectiveThe aim of this study was to determine whether systemic levels of miRNAs abundant in blood, including the neuroendocrine tissue-enriched miR-375, are altered in response to a glucose challenge.DesignTwelve healthy males were recruited for an acute crossover study that consisted of two tests each following an 8-hour fasting period. An oral glucose tolerance test (OGTT) was performed, and blood samples were collected over a 3-hour period. Following a period of at least 1 week, the same participants were administered an isoglycemic intravenous glucose infusion (IIGI) with the same blood-collection protocol.ResultsThe glucose response curve following the IIGI mimicked that obtained after the OGTT, but as expected, systemic insulin levels were lower during the IIGI compared with the OGTT (P < 0.05). miR-375 levels in circulation were increased only in response to an OGTT and not during an IIGI. In addition, the response to the OGTT also coincided with the transient increase of circulating glucagon-like peptide (GLP)-1, GLP-2, and glucose-dependent insulinotropic polypeptide.ConclusionsThe present findings show levels of miR-375 increase following administration of an OGTT and, in light of its enrichment in cells of the gut, suggest that the gastrointestinal tract may play an important role in the abundance and function of this miRNA in the blood.In this study, we show, using a clinical cohort, the impact of glucose administered orally on miR-375 in the blood, suggesting a role for the gut in regulating miR-375 levels in systemic circulation.